Peran Lokasi dan Persepsi Harga terhadap Minat Beli Ulang Konsumen Mixue: Gaya Hidup sebagai Pemoderasi - Rada Dea Ananda Puspa; Abriandi; Sihar Tambun (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
This study aims to prove the effect of location and price perception on repurchase intention of Mixue con-sumers with lifestyle as a moderating variable. As many as 300 Mixue consumers contributed in filling out the questionnaire. Purposive sampling was used by setting the criteria for the respondent, namely between 10 and 25 years of age and having made a purchase more than once. SmartPLS 4 SEM is used to process data. The results in this study include location, price perception, and lifestyle variables all having a signi-ficant impact on repurchase intentions. However, lifestyle cannot moderate the influence of location on repeat purchases. Even though it can have a positive impact, lifestyle is not statistically significant in mode-rating the influence of price perceptions on repeat purchases. The conclusion in this study is that companies must innovate a product that meets the lifestyle expectations of customers with impulsive consumption. Apart from lifestyle, price perception also needs to be improved. Location variables also need to be consider-ed, such as being able to offer a safe parking area and a high level of cleanliness and comfort